Evaluating Median Nerve Cross Sectional Area via Ultrasound; A Comparative Study between Sonographers and Non-Sonographers - Shabbir, Khadija; Nasrullah, Tauseef; Younas, Muhammad Hammad; Shah, Loqman; Tariq, Maryam; Jameel, Eman; Shahid, Malaika (Indus Journal of Bioscience Research, 2025)
Background: Sonographers are at an increased risk of developing median nerve abnormalities due to repetitive hand movements and prolonged occupational strain. This study evaluate the median nerve cross-sectional area, fascicular pattern, shape, and mobility among sonographers and non-sonographers using ultrasonography. Objective: To evaluate median nerve cross-sectional area (CSA) via Ultrasound between sonographers and non-sonographers. Methodology: This was a cross-sectional analytical study conducted over a period of four months, from November 04, 2024 March 03, 2025 at the Radiology Department of Services Hospital, Lahore. The study included 60 participants, and data was analyzed using the Statistical Package for the Social Sciences (SPSS). Results: The majority of participants were male (60%), while 40% were female. Right-hand dominance was observed in 56.7% of participants. The most frequent years of experience was 16 years (11.7%). The fascicular pattern assessment showed that 66.7% of participants had an intact pattern in the right hand, whereas the left hand showed a higher proportion of disrupted patterns (56.7%). Regarding nerve shape, a flattened median nerve was found in 48.3% of participants for the right hand and 50% for the left hand. Nerve mobility evaluation indicated that 36.7% of participants had normal mobility in the right hand, while 33.3% showed nerve entrapment. In the left hand, nerve entrapment was more common (43.3%), followed by normal mobility (36.7%). Gender-based analysis revealed a trend toward a higher prevalence of flattened nerves in females compared to males, though statistical significance was not reached (p = 0.073). No significant association was found between gender and nerve mobility (p = 0.375). Conclusion: This study found a higher prevalence of intact fascicular patterns and normal nerve mobility in the right hand, while the left hand showed more disrupted patterns and nerve entrapment. Flattened median nerves were common in both hands, slightly more so in females, though not statistically significant. No significant link was found between gender and nerve mobility. Overall, the left hand appeared more prone to structural and functional nerve changes.